A little plaster, a lot of design, all abnegation: the instruction of crafts for the 19th century student workers - Henriques, António (Historia y Memoria de la Educación, 2021)
The thoughts, writings, and actions of the most informed Portuguese expert on artistic education of the 19th century and connoisseur of Portugal’s artistic treasures, the historian and pedagogue Joaquim de Vasconcelos (1849- 1936), guide us in our inquiry into the tenets of the struggle for the establishment of technical elementary schools and industrial art schools based on the discipline of drawing. This struggle for the dignification of decorative arts also promoted the establishment of art-industrial museums. This movement, initially assumed by England through the South Kensington Museum, and which had ramifications in France, Germany, and Austria, outlined the need to provide work for working class children and youth in the second half of the 19th century and to provide them with autonomy, dignity, and an escape from misery. What began as a revolution in the teaching of drawing would have major consequences for the appreciation of cultural heritage and its sponsorship by the European aristocracy and bourgeoisie, as well as in the will to return it to the masses, as an effect of the power of the ruling classes. The article discusses how this revolution, and the promotion of homemade arts, implied: i) an ideation of a nationalist heritage, supported by an international movement of countries; ii) a validation of the fine arts by the European aristocracies, to serve as inspiration for craftwork; iii) the beginning of the awareness of cultural heritage as a phenomenon of the popular masses; iv) the alleged fall of the authenticity value of the artistic pieces.